2013
DOI: 10.1007/s10815-013-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of assisted reproduction treatments on Spanish newborns: report of 14,119 pregnancies

Abstract: Purpose To investigate neonatal malformation, prematurity, and stillbirth in singleton and multiple pregnancies derived from different Assisted Reproductive Techniques (ART). Methods In this prospective cohort study data were collected, from private and public Spanish IVF units, during the years 2008 and 2009. During this period, 8,682 pregnancies were analysed from the initial 14,119 pregnancies reported. Pregnancies included in the study derived from IUI (n=1,065), IVF (n=838), ICSI (n=5,080), FET (n=1,404) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(53 reference statements)
3
3
0
Order By: Relevance
“…This study found an incidence of 12% for prematurity in singleton pregnancies, very similar to the rate reported for other cohorts of assisted reproductive technology babies (Levi Setti et al, 2016;Ricciarelli et al, 2013). Among multiple pregnancies, 45% had premature delivery, which is consistent with the 42 − 68% rate reported by other European countries (Ricciarelli et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study found an incidence of 12% for prematurity in singleton pregnancies, very similar to the rate reported for other cohorts of assisted reproductive technology babies (Levi Setti et al, 2016;Ricciarelli et al, 2013). Among multiple pregnancies, 45% had premature delivery, which is consistent with the 42 − 68% rate reported by other European countries (Ricciarelli et al, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The percentage of stillbirth observed was similar to that reported for assisted reproductive technology pregnancy (Bonduelle et al, 2002;Koudstaal et al, 2000;Ricciarelli et al, 2013;Westergaard et al, 1999). It seems to be slightly, but not significantly, higher than the observed in natural conceptions (Fedder et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Thirty‐four studies met inclusion criteria (Figure 1). 23–54 There were 33 cohort studies and one case‐control study. No randomized trials were identified and no isolated abstracts or unpublished studies were identified that met eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Most newborns conceived through ART are healthy, but these have also been associated with higher rates of adverse obstetric and perinatal outcomes [7][8][9]. Concern about the safety of reproductive techniques and their effect on foetal/ maternal well-being is growing [10].…”
Section: Introductionmentioning
confidence: 99%